1995
DOI: 10.1007/bf02599570
|View full text |Cite
|
Sign up to set email alerts
|

Changes in study design, gender issues, and other characteristics of clinical research published in three major medical journals from 1971 to 1991

Abstract: Several important changes in clinical research studies published in JAMA, Lancet, and NEJM have taken place between 1971 and 1991. Clinical trials have increased in frequency, largely replacing studies containing ten or fewer subjects. Health services research has increased in prevalence, reflecting growing interest in studies addressing the delivery of health care. Our data support the hypothesis that exclusion of women from clinical research studies is an important contributor to the paucity of data concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
2
25
1
3
Order By: Relevance
“…However, limiting the analysis to the 384 clinical research papers revealed that cross-sectional studies comprised 53.9% of the oral and maxillofacial radiology clinical studies, which is greater than the 22%-44% of clinical research papers published in the general medical literature between 1946 and 1991 that were crosssectional studies. 7,8 Cohort and case-control studies combined comprised 2.1% of our total study sample of 725 papers, which is comparable with the 2% found in the paediatric dentistry literature. 22 Experimental studies comprised only 1% of our total sample, whereas they comprise 9% of the paediatric dentistry literature 22 and 17% of the English-language literature regarding therapy for temporomandibular disorders.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, limiting the analysis to the 384 clinical research papers revealed that cross-sectional studies comprised 53.9% of the oral and maxillofacial radiology clinical studies, which is greater than the 22%-44% of clinical research papers published in the general medical literature between 1946 and 1991 that were crosssectional studies. 7,8 Cohort and case-control studies combined comprised 2.1% of our total study sample of 725 papers, which is comparable with the 2% found in the paediatric dentistry literature. 22 Experimental studies comprised only 1% of our total sample, whereas they comprise 9% of the paediatric dentistry literature 22 and 17% of the English-language literature regarding therapy for temporomandibular disorders.…”
Section: Discussionsupporting
confidence: 69%
“…In 1991, a follow-up analysis based on the same three journals revealed an increase in the use of strong research designs. 8 From 1971 to 1991, clinical trials increased from 17% to 35% and case series decreased from 30% to 4%. No changes were noted in cross-sectional, cohort or case-control studies.…”
Section: Introductionmentioning
confidence: 99%
“…The types of statistical designs/methods and the quality of statistical and methodological reporting in medical publications have been established in anesthesia [47] , internal medicine [48] , bone and joint surgery [49] , clinical trials [50] , otolaryngology [51] , rehabilitation [52,53] , ophthalmology [54] , as well as for abstracts [55,56] and various journals: Transfusion [57] , New England Journal of Medicine [58,59] , Arthritis and Rheumatism [60] , and Chinese medical journals [61] . …”
Section: Discussionmentioning
confidence: 99%
“…But as early as the 1990s, case reports and series were losing favor among general medical journals. Among JAMA, NEJM, and Lancet, the proportion of case reports decreased from 42% to 8% from 1971-1991 [2]. Some journals, such as the BMJ, refuse to publish them.…”
mentioning
confidence: 99%